English Speaking Strategies by EFL Learnerss to Enhanche Self-Efficacy - Tauchid, Ahmad (Jurnal Ilmiah Pendidik Indonesia, 2023)
In the complex tapestry of human interaction, spoken communication remains an essential and timeless aspect of our social fabric. The study of spoken communication holds deep significance, exploring the core of human connection and interaction. The ability to express thoughts, emotions, and ideas verbally is fundamental for identity expression, relationship building, and navigating social complexities. While numerous researchers have contributed valuable insights to the study of spoken communication, a notable gap exists in strategies for English speaking tailored to diverse learner profiles. Existing studies offer general strategies for improving English speaking skills, yet they often neglect individual differences, learning styles, and cultural backgrounds. The proposed research seeks to address this gap by investigating and identifying personalized methodologies that enhance language acquisition for individuals with diverse linguistic backgrounds, learning styles, and cultural contexts. Conducted at Universitas Nahdlatul Ulama Sunan Giri, Bojonegoro, the study involved 40 student participants from the English language department, utilizing semi-structured interviews for data collection. Employing a descriptive qualitative research approach, the investigation found that sequential speaking learning strategies used by English as a Foreign Language (EFL) learners to enhance self-efficacy in an English classroom. These strategies encompass cognitive, affective, memory, social, and metacognitive approaches, revealing a notable absence of the compensation strategy among EFL learners. The research contributes to the understanding of nuanced approaches to spoken English, shedding light on effective strategies personalized to individual needs and addressing a crucial gap in existing studies.